Quality of services through public perception at Community Polyclinic, Peringgit, Melaka / Diyana Iskandar Zurkarnain and Nurazlin Ahmad - Iskandar Zurkarnain, Diyana; Ahmad, Nurazlin (Faculty of Administrative Science and Policy Studies, 2011)
Service quality is the perception that results from comparing expectation with the experience. It also become as the function of both process and outcomes. The service quality is a attitude formed by long-term evaluation of performance. There are five dimensions or factors that involved in service quality which is tangible, reliability, assurance, empathy and also responsiveness. All the factors have their own important roles towards the perception from the public. The study is made to identify the quality service through public perception at Community Polyclinic, Peringgit, Melaka. 110 respondents were taken which are the patients that came to Community Polyclinic, Peringgit, Melaka to seek for treatment. In Community Polyclinic, Peringgit, Melaka the number of patients that come per day are almost 1000 patients. This is based on the interview from the staff at the polyclinic itself. The most factor that affected to the public perception is empathy where it is based on the staff willingness in order to help the patients in terms of give feedback, give accurate information and also greet them. The instinct behaviors like obedience, loyalty and also advocacy participate in the service quality. The quality service become as the important component in deciding the perception from the public.